Telehealth for Children With Epilepsy Is Effective and Reduces Anxiety Independent of Healthcare Setting - Klotz, Kerstin Alexandra; Borlot, Felippe; Scantlebury, Morris H.; Payne, Eric T.; Appendino, Juan Pablo; Schönberger, Jan; Jacobs, Julia (Frontiers in Pediatrics, 2021)
Objectives: The use of telemedicine use has grown exponentially as an alternative to providing care to patients with epilepsy during the pandemic. We investigated the impact of the current pandemic among children with epilepsy from two distinct pediatric epilepsy centers. We also compared perceptions among those who received telemedicine against those who did not. Methods: We developed a questionnaire and invited families followed in Freiburg, Germany and Calgary, Canada to participate during the initial nine months of the pandemic. The survey contained 32 questions, 10 of which were stratified according to telemedicine exposure. Results: One hundred twenty-six families (80 in Freiburg, 46 in Calgary) participated and 40.3% received telemedicine care. Most children (mean age 10.4 years, SD 5.1) had chronic epilepsy, but poorly controlled seizures. Negative impacts were reported by 36% and 65% of families who had to re-schedule appointments for visits and diagnostics, respectively. Nearly two thirds of families reported no change in seizure frequency, while 18.2% reported either worsening or improvement of seizures. Although most families did not note behavioral changes, 28.2% reported behavior worsening. Families who received telemedicine care had a statistically significant reduction of parental self-reported anxiety level after virtual visits compared to those who did not experience telemedicine. Families with telemedicine consultations were more likely to consider future virtual care (84% vs. 65.2% of those without), even after the pandemic. Patient data safety, easy access to specialized services, and consistency with the same healthcare provider were graded as important in both centers, while a shorter waiting time was most relevant in Calgary. Conclusion: In our cohort, some children with epilepsy experienced increased seizures worsening behavioral during the first nine months of the current pandemic. In addition, our data suggest that telemedicine might reduce parental anxiety symptoms and families who experienced telehealth were more positive and open to similar appointments in the future.